Bitter Orange - Hodge, W. (Stephens Ltd., Trinidad, 2009)
A picture of a bunch of oranges on a branch, Bitter Orange is also known as Sour Orange.
Colour: Coloured; Style: Portrait; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Fruit--Trinidad and Tobago; Oranges; Citrus fruits--Trinidad and Tobago